Intermediary Biotechnology Service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
National agricultural research systems (NARS) in developing countries now have access to the first comprehensive database of information on international biotechnology programmes related to agriculture. The database was compiled by the Intermediary...